2017
DOI: 10.1016/j.pedneo.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Heated Humidified High-flow Nasal Cannula as Noninvasive Respiratory Support in Neonates

Abstract: Recently, heated humidified high-flow nasal cannula (HHHFNC) has been introduced and applied as a noninvasive respiratory support in neonates. Although HHHFNC is widely used in neonates presenting with respiratory distress, the efficiency and safety when compared with nasal continuous positive airway pressure or noninvasive positive pressure ventilation are still controversial. This review aims to evaluate the performance and applications of HHHFNC in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
0
18
0
2
Order By: Relevance
“…7 Despite the lack of data about the use of HHFNC in NICU settings, HHFNC has been widely used because of advantages in terms of fixation techniques, positional problems, and nasal trauma. 8,9 Recent studies have demonstrated that HHFNC is as effective as other non-invasive respiratory support for preterm infants for reducing adverse outcomes. 10 However, there is still insufficient evidence to support the effectiveness and safety of HHFNC in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…7 Despite the lack of data about the use of HHFNC in NICU settings, HHFNC has been widely used because of advantages in terms of fixation techniques, positional problems, and nasal trauma. 8,9 Recent studies have demonstrated that HHFNC is as effective as other non-invasive respiratory support for preterm infants for reducing adverse outcomes. 10 However, there is still insufficient evidence to support the effectiveness and safety of HHFNC in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…[61516] Heated humidified high-flow nasal cannula (HHHFNC) is another technique of respiratory support in neonates with RDS, which is recently considered due to its ease of use, better tolerance, improved nutrition, increased maternal–infant bonding, and less iatrogenic injury. [1718] However, based on the results of the current study, there is still no study on its efficacy as a primary treatment for neonates with RDS. Therefore, the current study aimed at comparing the strength of HHHFNC respiratory management with the standard treatment of RDS disease (NCPAP), as well as noninvasive NIMV technique, and also other primary and secondary clinical outcomes of the three mentioned techniques.…”
Section: Introductionmentioning
confidence: 94%
“…HFNC improves pulmonary function by providing positive distending pressure [7] to increase functional residual capacity and improve alveolar recruitment [8]. It also provides nasopharyngeal dead space washout, nasopharynx distension [8,9], decreased work of breathing [10], and improves gas exchange. In addition, the warmed, humidified air to the conducting airways improves pulmonary compliance and conductance [5,8].…”
Section: Am J Biomed Sci and Resmentioning
confidence: 99%